Exploring the Influence of Intercultural Work Culture on Employee Productivity in Multinational Companies - Andriyani, Erita; Syamsunasir, Syamsunasir (Dinasti Publisher, 2025)
A cross-cultural work culture within a multinational company plays a crucial role in determining employee effectiveness and productivity. Cultural diversity in the workplace can provide benefits in the form of innovation and work efficiency, but also presents communication challenges and differences in values and norms. This study aims to analyze the impact of cross-cultural work culture on employee productivity in multinational companies. Using a phenomenological qualitative approach, data was collected through in-depth interviews and participatory observation of employees working in a multicultural environment. The results showed that cultural diversity encourages creativity and team effectiveness, but also causes communication and adaptation barriers that affect individual performance. It was found that companies that implemented flexible management strategies and cross-cultural training programs were able to improve the effectiveness of employee communication and collaboration. The conclusion of this study emphasizes the importance of management's role in managing cultural diversity in order to become a competitive advantage for the company.